Pastoral theology and care: critical trajectories in theory and practice - Ramsay, Nancy J. (Wiley Blackwell, 2018)
Practice matters : new directions in ethnography and qualitative research / Mary Clark Moschella -- How the brain matters / David Hogue -- Class power and human suffering : resisting the idolatry of the market in religious practice and pastoral theology / Bruce Rogers-Vaughn -- Postcolonializing pastoral theology : enhancing the intercultural paradigm / Emmanuel Y. Amugi Lartey -- Caring from a distance : intersectional pastoral theology amid plurality regarding spirituality and religion / Kathleen J. Greider -- Black women's experience of religion and sexuality in womanist pastoral theology / Phillis Isabella Sheppard -- Analyzing and engaging asymmetries of power : intersectionality as a resource for practices of care / Nancy J. Ramsay